2014
DOI: 10.1136/bmjspcare-2014-000696
|View full text |Cite
|
Sign up to set email alerts
|

Place of care: from referral to specialist palliative care until death

Abstract: A significant number of patients received specialist palliative care across multiple care settings. Late referral is associated with a single domain of care. General practitioner involvement supports patient care and death at home. Place of care and ease of transfer between care settings may be better indicators of the quality of care we provide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Palliative care in the home interventions were evaluated with the primary outcomes of resource use, cost, or place of death in nearly one third of included studies. Some have argued that these outcomes are not sufficient to assess the effectiveness of the intervention [ 54 , 55 ]. The effectiveness measure should link to the objective of the intervention; place of death may be a less appropriate outcome than the location of care preceding death [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palliative care in the home interventions were evaluated with the primary outcomes of resource use, cost, or place of death in nearly one third of included studies. Some have argued that these outcomes are not sufficient to assess the effectiveness of the intervention [ 54 , 55 ]. The effectiveness measure should link to the objective of the intervention; place of death may be a less appropriate outcome than the location of care preceding death [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some have argued that these outcomes are not sufficient to assess the effectiveness of the intervention [ 54 , 55 ]. The effectiveness measure should link to the objective of the intervention; place of death may be a less appropriate outcome than the location of care preceding death [ 55 ]. Our findings underscore the need to expand outcome measurement beyond routinely collected data to measure outcomes that are more tightly linked to the objective of palliative care in the home.…”
Section: Discussionmentioning
confidence: 99%
“…In an economic evaluation of specialist palliative care services in three parts of Ireland which have heterogeneous structures and resources for these services, Brick et al found that an area with well-developed specialist palliative care services and, where its role is understood, is likely to have more referrals and that these will in general be earlier [ 40 ]. O’Leary et al, in a study of one specialist palliative care service in Ireland over a 6-month period found late referral to palliative care was associated with receiving specialist palliative care in one care setting only but receiving care across multiple settings supported people to stay at home for longer [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is however possible to broadly categorise the literature into those studies reporting exposure to hospital-based palliative care services and those reporting community or hospice-based services. Studies from the UK,16 17 the USA,18 19 Korea20 and Singapore21 report the median duration of HPC to range from 14.4 to 57 days and studies reporting CPC from Canada,22 Italy15 and Ireland7 report duration to range from 40 to 70 days. These studies provide useful context to the data reported here (20 days to HPC; 46 days CPC) and show the timing of referral to be consistent with that reported in the international literature.…”
Section: Discussionmentioning
confidence: 99%
“…Following a randomised phase III trial in patients with small cell lung cancer, which demonstrated the benefit of early palliative care involvement in terms of quality of life and survival in 2010,1 the American Society of Clinical Oncology issued guidance recommending that palliative care should be considered early in the course of illness for any patient with metastatic cancer or high symptom burden 7. Despite this growing evidence base, within routine clinical practice in the UK palliative care clinicians report that many referrals are made in the last weeks or days of life.…”
Section: Introductionmentioning
confidence: 99%